Pemanfaatan Media Animasi dalam Pembelajaran Fikih pada Kurikulum Merdeka Belajar di Madrasah Ibtidaiyah: Tinjauan Teoretis: Studi Kasus di Nunukan - Amin Rais (Yayasan Syamil Quran Nunukan, 2024)
This study aims to theoretically examine the use of animation media in fiqh learning in the Independent Learning Curriculum at the Madrasah Ibtidaiyah level, with a focus on studies in madrasas in the Nunukan area. Using a qualitative approach of the type of literature study, data were obtained from relevant literature, books, journals, and previous research results. The results of the study show that animation media is able to increase the effectiveness of fiqh learning through abstract concept visualization, increase student motivation, and support the application of differentiated learning according to the principles of the Independent Curriculum. Theories such as Cognitive Theory of Multimedia Learning (Mayer), Discovery Learning (Bruner), and Sociocultural Theory (Vygotsky) support the use of these media in improving students' cognitive, affective, and social understanding. However, challenges in the form of limited technological facilities, internet access, and teacher training needs are still obstacles in its implementation, especially in border areas such as Nunukan. Therefore, synergy is needed between teachers, madrasas, and policy makers to optimize the potential of animation media as an innovation in Islamic education in the digital era. The use of animation media in fiqh learning is considered strategic in forming a generation of Muslims who are intelligent, creative, and applicative in accordance with the demands of the 21st century.